Knowledge Attitude and Practice of Food Handlers Regarding Food Safety Practices District Kohat Khyber Pakhtunkhwa Pakistan - Muhammad Jibran Khan, Naeemullah, Nadia Khan, Anwar Khan Wazir, Arif Iqbal, Muhammad Ishtiaq, Said Akbar Khan, Jawad Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the knowledge, attitude and practice of food handlers regarding food safety and personnel hygiene practices among the local food handlers of District Kohat Khyber Pakhtunkhwa Pakistan. Methodology: The Department of Community Medicine at the KMU-Institute of Medical Sciences (KIMS), Kohat, conducted a cross-sectional study between December 2021 and May 2022. A cross-sectional study with a sample of n=265 adults was conducted, with a 95% confidence interval and a 5% margin of error. The respondents’ food safety knowledge, attitudes, and behaviours were evaluated using a well-designed questionnaire. Data were entered and analysed using SPSS version 26.0. Final results were tabulated and presented. Results: Out of those surveyed, 39.25% were found to have a basic understanding of the written word; 82.648% earned less than 30,000 PKR per month; 58.87% had worked for at least four years; and 67.74% were in the service industry (mostly as cooks and wait staff). In addition, 32.83 percent of those who handled the food had adequate expertise, 90.94 percent had an upbeat mentality, and 47.92 percent followed adequate procedures to ensure the safety and cleanliness of the food they handled. Conclusions: It was concluded that knowledge of food handlers was not up to the standards of food safety and personnel hygiene practices. Moreover, the attitude of food handlers was satisfactory whereas the practice was below the average satisfactory level and thus needs strategies to enhance knowledge, and to improve practices of food handlers regarding food safety to reduce food borne diseases. Keywords: Knowledge, Food Contamination, Practice, Food Handlers, Attitude, Kohat.